Tracing Diabetes Mellitus Readmission Incidence Through Medical Records at Bhayangkara Hospital, Bengkulu - Budiarti, Anggia; Heltiani, Nofri (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2025)
Readmission can occur for all diseases, including diabetes mellitus. A preliminary survey showed an increase in readmission rates over the past three years. If readmissions occur more than once within a 30-day period, and within a short period of time, the hospital cannot claim funding. The BPJS (Social Security Agency) claims payment system for healthcare services is based on a per-case payment within a predetermined timeframe of ≤30 days. If the time limit is exceeded, the hospital bears the costs. The purpose of this study was to determine the incidence of diabetes mellitus readmissions at Bhayangkara Hospital, Bengkulu. This study was a descriptive quantitative study, with 25 medical records of inpatient diabetes mellitus readmissions collected from January to December 2023 as the population and sample. The data used in this study were secondary data using observation sheets. The data were then processed and analyzed univariately using frequency distribution. The results of the study showed that the incidence of readmission of diabetes mellitus was 100% with the majority being 48% in the 56 - ≥65 years age group, 64% female gender and 52% family history of the disease.